Impact of a Rheumatology Clinic Protocol on Tobacco Cessation Quit Line Referrals. Issue 9 (27th May 2022) - Bartels, Christie M.; Johnson, Lauren; Ramly, Edmond; Panyard, Daniel J.; Gilmore‐Bykovskyi, Andrea; Johnson, Heather M.; McBride, Patrick; Li, Zhanhai; Sampene, Emmanuel; Lauver, Diane R.; Lewicki, Kristin; Piper, Megan E.
Abstract : Objective: Smoking increases cardiopulmonary and rheumatic disease risk, yet tobacco cessation intervention is rare in rheumatology clinics. This study aimed to implement a rheumatology staff‐driven protocol, Quit Connect, to increase the rate of electronic referrals (e‐referrals) to free, state‐run tobacco quit lines. Methods: We conducted a quasi‐experimental cohort study of Quit Connect at 3 rheumatology clinics comparing tobacco quit line referrals from 4 baseline years to referrals during a 6‐month intervention period. Nurses and medical assistants were trained to use 2 standardized electronic health record (EHR) prompts to check readiness to quit smoking within 30 days, advise cessation, and connect patients using tobacco quit line e‐referral orders. Our objective was to use EHR data to examine the primary outcome of tobacco quit line referrals using pre/post design. Results: Across 54, 090 pre‐ and post‐protocol rheumatology clinic visits, 4, 601 were with current smokers. We compared outcomes between 4, 078 eligible pre‐implementation visits and 523 intervention period visits. Post‐implementation, the odds of tobacco quit line referral were 26‐fold higher compared to our pre‐implementation rate (unadjusted odds ratio [OR] 26 [95% confidence interval (95% CI) 6–106]). Adjusted odds of checking readiness to quit in the next 30 days increased over 100‐fold compared to pre‐implementation (adjusted OR 132 [95% CI 99–177]). Intervention led to e‐referrals for 71% of quit‐ready patients in <90 seconds; 24% of referred patients reported a quit attempt. Conclusion: Implementing Quit Connect in rheumatology clinics was feasible and improved referrals to a state‐run tobacco quit line. Given the importance of smoking cessation to reduce cardiopulmonary and rheumatic disease risk, future studies should investigate disseminating cessation protocols like Quit Connect that leverage tobacco quit lines.